Primary Cardiac Hemangiosarcoma in a Dog - Long Survival Time after Auriculectomy - Scalzilli, Bruna; de Paula Reis Filho, Nazilton; Soares Lopes, Camilla; Soares dos Santos, André Luís; Vieira Martins, Gislaine Regina; Gonçales Guzzo, Marcela; Pereira Toscano, Cauê; Herreira Jarrouge, Daniel (Acta Scientiae Veterinariae, 2025)
Background: Cardiac tumors are rare in dogs, with an incidence of up to 0.19%, and hemangiosarcoma represents the most frequently diagnosed neoplasm. This malignancy of vascular endothelial origin is characterized by its aggressive behavior, high invasiveness, and significant metastatic potential. Although its occurrence is uncommon, prompt recognition and timely intervention are essential to improve clinical outcomes. This report details the case of a dog diagnosed with primary cardiac hemangiosarcoma that underwent right auriculectomy, resulting in a survival time surpassing reported averages. Case: A 6-year-old male mixed-breed dog presented with a history of syncope due to cardiac tamponade caused by pericardial effusion secondary to a cardiac mass. Hematological analyses, abdominal ultrasound, and coagulation profiles were unremarkable. Advanced imaging, including echocardiography and thoracic computed tomography, identified a right auricular mass measuring 4.9 × 3.7 × 2.0 cm, with no evidence of metastatic disease. A right intercostal thoracotomy and subphrenic pericardiectomy were performed, exposing the tumor adherent to the pericardial sac. The mass was excised by ligating its base with 0 polypropylene sutures, followed by closure of the myocardial defect using 2-0 polypropylene in a simple continuous pattern to control bleeding. A thoracic drain was placed, and the thoracotomy was closed using a simple interrupted pattern with 2-0 polyglactin 910. Postoperatively, the thoracic drain was removed after 72 h, and the dog was discharged. Histopathological evaluation confirmed the diagnosis of hemangiosarcoma. Chemotherapy with doxorubicin (1 mg/kg, IV) was administered every 21 days for 6 cycles, followed by metronomic chemotherapy with cyclophosphamide (15 mg/m²) and piroxicam (0.3 mg/kg) administered orally on alternate days for 6 months. Follow-up evaluations conducted quarterly have revealed no evidence of metastatic progression. At 1-year post-surgery, the dog remains clinically healthy and asymptomatic, representing a survival time significantly longer than typically observed in similar cases. Discussion: Primary cardiac tumors account for approximately 84% of cases in dogs, as exemplified in this report. While purebred dogs are often overrepresented, this case involved a 6-year-old mixed-breed dog, which falls within the typical age range of 7-15 years for cardiac hemangiosarcoma (HSA). HSA is a highly aggressive malignancy associated with poor prognosis, commonly presenting with clinical signs such as pericardial effusion, cardiac tamponade, and syncope. Median survival times for dogs with cardiac HSA are generally limited, ranging from weeks to a few months, even with treatment. Remarkably, the patient in this case has achieved over 500 days of survival without metastatic disease, despite literature reporting that up to 62% of dogs with cardiac HSA present with metastases at diagnosis. Surgical management involving pericardiectomy and auriculectomy enabled complete tumor removal without complications, and adjuvant chemotherapy further contributed to the extended survival. This case highlights the importance of advanced diagnostic imaging for precise surgical planning and underscores the potential benefits of a multimodal treatment approach. Given the poor prognosis typically associated with cardiac HSA, continued exploration of innovative therapies and aggressive surgical interventions is warranted. This case also reinforces the role of surgery in improving outcomes, challenging the perception that cardiac hemangiosarcoma is invariably fatal and suggesting that surgery may help prevent premature euthanasia in select cases. Keywords: canine, vascular endothelium, cardiac neoplasia, auricle. Título: Hemangiossarcoma cardíaco primário em um cão - longo tempo de sobrevivência após auriculectomia Descritores: canino, endotélio vascular, neoplasia cardíaca, aurícula.